P62 mutations, ubiquitin recognition and Paget's disease of bone. (25th October 2006) - Layfield, R.; Cavey, J.R.; Najat, D.; Long, J.; Sheppard, P.W.; Ralston, S.H.; Searle, M.S.
Abstract : Functional analyses of PDB (Paget's disease of bone)-associated mutants of the p62 [also known as SQSTM1 (sequestosome 1)] signalling adaptor protein represent an interesting paradigm for understanding not only the disease mechanism in this skeletal disorder, but also the critical determinants of ubiquitin recognition by an ubiquitin-binding protein. The 11 separate PDB mutations identified to date all affect the C-terminal region of p62 containing the UBA domain (ubiquitin-associated domain), a ubiquitin-binding element. All of these mutations have deleterious effects on ubiquitin binding by p62 in vitro, and there is evidence of an inverse relationship between ubiquitin-binding function and disease severity. The effects on ubiquitin-binding function of most of the mutations can be attributed to either reduced UBA domain stability, and/or the mutations affecting the presumed ubiquitin-binding interface of the UBA domain. However, a subset of the mutations are more difficult to rationalize; several of these affect sequences of p62 outside of the minimal ubiquitin-binding region, providing insights into non-UBA domain sequences within the host protein which mediate ubiquitin-binding affinity. The p62 mutations are presumed to result in activation of (osteoclast) NF-κB (nuclear factor κB) signalling. Understanding how loss of ubiquitin-binding function of p62 impacts on signal transduction events in osteoclasts will undoubtedly further our understanding of the disease mechanism in PDB at the molecular level.